The 3D plan analysis under progressive collapse for RC buildings through demand capacity ratio (DC) for three levels of damage - Mushina, Wissam; Mushina, Jalal (Edelweiss Applied Science and Technology, 2024)
The progressive collapse presents a sudden load may cause initial failure in local parts at the frame which could lead to sequence reactions in the elements of the structure. A building of seven storeys was chosen to designed under gravity load according ACI 318 Code. This building is analyzed under progressive collapse condition for two columns damage cases; edge damage, corner damage. The building needs to be loaded as specified according (GSA) General Services Administration requirements through linear static analysis. The results of linear analysis show the variation in ((DC)) demand capacity ratio for the columns. The aspects of damage action in this study regarding section size and damage cases with 100% damage column loss (full damage), 60% damage (0.6 section size), 80% damage (0.8 section size). A GSA guideline to typical building with (DC) values bigger than 1.5 refer to critical potential damage conditions at the columns of the frame. It can be seen of the results the effect of size reduction for the building. This effect is clear to be decreased along distance from any plan. The((DC)) for columns which exceeded 1.5 value which show risky damage condition could actually happened that present serious threat possibility specially for nominated columns C22, C29 and C23 at plans A and B which show middle columns at lower position of the building.